RIVERINE CATFISHES OF KALIMANTAN, PANGASIIDAE: DIAGNOSIS, DISTRIBUTTON, AND ECOLOGY - Rudhy Gustiano; Laurent Pouyaud (Indonesian Fisheries Research Journal, 2005)
The main constrain to cultivate wild species and optimize the production of cultured species is to due poorly documented of genetic resources. ln the current study, it presents the diversity of pangasiids catfishes from Kalimantan.